2004
DOI: 10.1203/01.pdr.0000132837.29067.0e
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Enzymatic and Phenotypic Correction in the Phenylketonuria Mouse Model by Adeno-Associated Virus Vector-Mediated Gene Transfer

Abstract: Phenylketonuria (PKU) is an autosomal recessive metabolic disorder caused by a deficiency of phenylalanine hydroxylase (PAH). The accumulation of phenylalanine leads to severe mental and psychomotor retardation, and hypopigmentation of skin and hair. Low-phenylalanine diet therapy can prevent irreversible damage if instituted from birth. However, poor compliance with the strict lifelong dietary therapy leads to various neurologic and behavioral problems. To develop a safe and promising gene therapy method for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 28 publications
(31 reference statements)
2
34
0
Order By: Relevance
“…When comparing the Phe concentrations of male and female PKU mice, we found that the Phe concentrations in females were slightly but not significantly higher than in males (males: 16957385 mM, n ¼ 21; females: 18667256 mM, n ¼ 22; P-value 0.0997). This reflects to some extent the disagreement published by Mochizuki et al 27 in comparison with the publication by Oh et al 28 with regard to sex-dependent blood Phe concentrations in PKU mice (see also discussion below).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…When comparing the Phe concentrations of male and female PKU mice, we found that the Phe concentrations in females were slightly but not significantly higher than in males (males: 16957385 mM, n ¼ 21; females: 18667256 mM, n ¼ 22; P-value 0.0997). This reflects to some extent the disagreement published by Mochizuki et al 27 in comparison with the publication by Oh et al 28 with regard to sex-dependent blood Phe concentrations in PKU mice (see also discussion below).…”
Section: Resultsmentioning
confidence: 93%
“…In summary, we found after injection of 5 Â 10 12 vector genomes per mouse approximately 10 3 rAAV copies per transduced hepatocyte which is comparable to Nakai et al 25 that reported a transduction rate of around 620 copies in liver cells for 7.2 Â 10 12 vector genomes per injected mouse. Unfortunately, transduction rates of rAAV in liver of PKU mice were not reported for the treatments published by Mochiziki et al 27 or Oh et al 28 Serum hepatic and renal parameters (alanine aminotransferase ALT, aspartate aminotransferase AST, and gamma-glutamyltranspeptidase gGT), as well as inflammation parameters (interleukin-12 (IL-12) and tumor necrosis factor-a (TNF-a)) did not show any significant increase at 4 and at 20 weeks after portal or tail vein injections (not shown). This indicated that there was neither liver damage nor toxicity in rAAV vector-treated mice, which is also in agreement with reports from others.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific examples that have been investigated as therapeutic targets using rAAV include ornithine transcarbamylase (OTC) deficiency, 55 phenylketonuria (PKU) [56][57][58][59] homocytinuria, 60 methylmalonic aciduria (MMA) 61 and Canavan disease, 62,63 a cerebral organic aciduria.…”
Section: Disorders Of Amino Acid and Protein Metabolismmentioning
confidence: 99%
“…Similar to results achieved for OTC deficiency, relatively robust phenotype correction has been achieved in mice, albeit more effective and durable in males, possibly as a consequence of higher initial levels of transduction. [56][57][58][59] The weakness of PKU as a target for gene therapy is the availability of effective dietary therapy.…”
Section: Disorders Of Amino Acid and Protein Metabolismmentioning
confidence: 99%